Exploratory analysis of the scale of Sternberg love in university Peruvian students [Análisis exploratorio de la escala de amor de Sternberg en estudiantes universitarios peruanos ] - Ventura León, José Luis (2016)
ABSTRACT The article describes the properties psicométricas of the Triangular Scale of the Love of Sternberg (1986) (ETAS). The scale was administered to 455 university students of Metropolitan Lima, 145 males and 310 women, whose ages ranged between 16 to 51 years. The results reveal a reliability, by means of Cronbach’s alfa, for the total scale of .964. The factors intimidate, commitment and passion present indexes of reliability of .947.922 and.848 respectively. All the coefficients of reliability are considered to be excellent. The analysis factorial exploratorio suggested that they are three factors those that sublie to the articles, though there is evidence of the existence of an alone factor. One concludes that the ETAS presents suitable properties psicométrica, an analysis being recommended to realize factorial confirmatory in order to check the internal structure.